Detox Media Social Instagram Pada Generasi Z - Zahrah, Yusro Sakinatu; Toruan, Rialdo Rezeky Manogari Lumban; Wiyati, Eni Kardi (Brand Communication, 2025)
This study investigates the underlying reasons and contributing factors leading Generation Z to develop an addiction to Instagram, examines the manifestations of Fear of Missing Out (FoMO) behaviors, and explores effective strategies for social media detoxification. Employing a descriptive qualitative method with a case study approach, data were collected through semi-structured interviews with four Generation Z Instagram users—two who are currently experiencing FoMO and two who have successfully overcome it. The findings reveal several factors contributing to Instagram addiction: unhealthy usage patterns, the use of Instagram as an escape from daily stressors, the pursuit of pleasure and emotional satisfaction through content interaction, self-pride derived from positive social feedback, emotional reactions such as euphoria or frustration triggered by online content, and Instagram's role as a substitute for real-world social interactions. FoMO behavior is identified as stemming from the persistent desire to remain updated on others’ activities. Social media detoxification strategies are categorized into slow and fast approaches: the slow approach emphasizes reducing usage time and enhancing self-regulation, while the fast approach involves total abstinence, improving mental health and well-being, and reinforcing social support systems.